Electrosprayed Chitosan Microcapsules as Delivery Vehicles for Vaginal Phytoformulations - Moreno, María Alejandra (2018)
The design of novel delivery systems to treat vaginal fungalinfections is a topic of high interest. Chitosan, being itselfantimicrobial and having good mucoadhesive properties, is an excellentcandidate as a delivery matrix for active compounds. In this work,chitosan microcapsules containing dry extracts of Argentinean medicinalplants with proved biological properties (Larrea divaricata, L.cuneifolia, L. nitida, Zuccagnia punctata and Tetraglochin andina) weredeveloped through electrospraying and compared with conventionally usedtablets containing the same extracts. Total phenolics(spectrophotometry), morphology and particle size (SEM), molecularorganization (FT-IR spectroscopy), water sorption capacity, release ofbioactive compounds (BC) and biological properties were assessed. Theencapsulation process did not degrade the BC, as antioxidant andantifungal capacity remained unchanged. The FT-IR analysis suggestedinteractions via hydrogen bonding or hydrophobic interactions between thechitosan and the extracts, which explained why the microcapsules kept theintegrity in slightly acidic media. Increased solubility of the extractswhen incorporated in the microcapsules was seen in simulated vaginalfluid, potentially increasing the bioavailability of BC in the vaginalenvironment. This work highlights the potential of the chitosan-baseddelivery systems for phytomedicines with antifungal and antioxidantactivity to be used in vulvovaginal candidiasis.